Timed sequential therapy for acute myelogenous leukemia: Results of a retrospective study of 301 patients and review of the literature. (October 2017) - Norsworthy, Kelly J.; DeZern, Amy E.; Tsai, Hua-Ling; Hand, Wesley A.; Varadhan, Ravi; Gore, Steven D.; Gojo, Ivana; Pratz, Keith; Carraway, Hetty E.; Showel, Margaret; McDevitt, Michael A.; Gladstone, Douglas; et al.
Highlights: Timed sequential therapy (TST) times a second drug with peak leukemia proliferation TST induction results were analyzed in 301 patients with newly diagnosed AML Results with TST in a non-clinical trial population resulted in favorable outcomes Abstract: Timed sequential therapy (TST) aims to improve outcomes in acute myelogenous leukemia (AML) by harnessing drug-induced cell cycle kinetics of AML, where a second drug is timed to coincide with peak leukemia proliferation induced by the first drugs. We analyzed outcomes in 301 newly diagnosed AML patients treated from 2004–2013 with cytarabine, anthracycline, and etoposide TST induction. Median age was 52 (range 20–74) and complete remission rate 68%. With median follow-up 5.8 years, 5-year DFS and overall survival (OS) were 37% (95% CI 31–45%) and 32% (95% CI 27–38%), respectively. In multivariate analysis, older age, unfavorable cytogenetics, and WBC ≥ 50 × 10 9 /L resulted in worse OS. Among patients not undergoing blood and marrow transplant, a propensity score analysis, which reduces imbalance in baseline characteristics, showed consolidation with TST compared with 1 or more cycles high-dose cytarabine trended toward lower DFS and post-remission survival with hazard ratio (HR) 1.9 (95% CI 0.9–4.0), and 1.6 (95% CI 0.7–3.6), respectively. Our results demonstrate the efficacy and feasibility of TST induction for newly diagnosed patients with AML, with results comparable to that seen in clinical trials with other TST therapies and 7 + 3.